Pengelolaan Lingkungan Melalui Izin Terintegrasi Dan Berantai: Sebuah Perbandingan Atas Perizinan Lingkungan Di Berbagai Negara - Wibisana, Muhammad Andri Gunawan (UI Scholars Hub, 2018)
Environmental permit is considered to play a central role in environmental management. There has been a growing intention in Indonesia for an integrated permit system, either in terms of internal integration, in which all environmental permits are integrated into a single permit, or external integration, in which environmental permits are integrated with business/activity license. This paper attemps to answer the questions of whether both ways of integrating environmental permits have been implemented in Indonesia. The paper also observes that although some contries have integrated various permits into a single environmental permit, the link between environmental permit and business/activity license remains unclear. More importantly, it is found that in many countries many business activities are not required to have a business license. For these activities, it might be the case that environmental permit is the only permit required, and hence, the revocation of the permit might result in the termination of the activities